PO.7.153 Systemic lupus-dermatomyositis overlapping syndrome: a case report. (27th September 2022) - Bouziani, N; Belabbas, A; Derder, M; Hakem, D
Abstract : Introduction: About 10 to 20% of myositis are associated with other connectivitis as cleroderma, Sjogren's syndrome and systemic lupus erythematosus (SLE). Nearly 10 to 15% - with specific immunological markers are associated with cancers. Purpose: To review a case report to illustrate this clinical situation Observation: A 53 years old woman, without medical history, who presented with arthromyalgia associated with a skin rash, all of which had been progressively evolving for 3 months. On clinical examination, a typical clinical myogenic syndrome was noted Skin involvement was also noted. erythematous macular lesions poorly limited, partly erosive, periorbital, erythema in shawl and V neckline on the upper limbs and neck with the presence of erosive pulpal lesions on the anterior surfaces of the fingers. There was also diffuse alopecia and butterfly-wing erythema of the face. In addition, a notion of intermittent fever at 38.5 with a progressive deterioration in general condition was reported. Severe signs such as dysphagia and dyspnea on the slightest exertion justified his admission to hospital. The physical examination found a BMI at 25, HR at 88 beats/min, respiratory rate at 20 cycles/min, TA at 110/70 mm Hg and saturation at rest and ambient air at 97%. Apart from the muscle damage, the examination of the various devices (lung, heart, vessels) was unremarkable. The biological explorations revealed leukopenia at 2000 with neutropenia and a lymphopenia at 600. The inflammatory syndrome was attested by an ESR of 59 mm and CRP of 12 mg/l. An elevation of muscle enzymes was noted (X8 N). The ANA and anti-DNA antibodies were positive but without other antigenic specificity. In addition, the blood ionogram, the renal assessment, the assessment of hemostasis were normal. Viral hepatitis (B and C) and covid 19 serologies were negative. The EMNG showed muscle damage. Cardiac evaluation objectified increase in troponins which remained stable over time with no noticeable alteration on the electrical tracing, but nevertheless apical hypokinesia without alteration of systolic function was found on cardiac echography-Doppler. At the end of these explorations, the diagnosis of overlap myositis was retained in front of the signs of dermatomyositis and SLE (the latter accumulated 19 points of the EULAR/ACR 2019 classification criteria). Therapeutically and in view of the severe motor deficit and cardiac involvement, the patient was put on a bolus of corticosteroids and immunoglobulin infusions. The evolution was favorable. The search for cancer (ovaries, lungs, breast, genitals) by the appropriate examinations (thoraco-abdominopelvic CT scan, mammography, cervico-vaginal smear) was negative, as were the anti-TIF1Y antibodies. Conclusion: The association SLE and inflammatory myopathy is rare and all types of myopathy can be found. There is a strong female predominance in so-called overlapping myositis. On the evolutionary level, the presence of another connective tissue does not seem to modify the response of myositis to treatment. The fear of cancer in its forms remains a low probability but nevertheless justifies clinical monitoring.